Biotransformation of natural hydroxycinnamic acids by gut microbiota from normal and cerebral ischemia-reperfusion injured rats: a comparative study. Issue 6 (29th May 2020) - Shen, Huihui; Tong, Xin; Yang, Jiehong; Yu, Li; Zhou, Huifen; Wang, Yu; He, Yu; Wan, Haitong; Li, Chang
Abstract : Hydroxycinnamic acids can undergo decarboxylation and dehydrogenation by gut microbiota from normal and cerebral I/R injured rats. Abstract : Hydroxycinnamic acids (HAs) are widely spread in food and herbal medicines. The bioavailability of HAs largely depends on the absorption and metabolism in enterohepatic circulation, in which gut microbiota plays a vital role. The present research aims to investigate the metabolism of HAs by gut microbiota, together with the community changes of gut microbiota after cerebral ischemia-reperfusion (I/R) injury. The results showed that non-substituted cinnamic acid (NCA) and sinapic acid (SA) were stable to gut microbiota, while 4-hydrocinnamic acid (4-HA), caffeic acid (CA), and ferulic acid (FA) underwent decarboxylation and hydrogenation after anaerobic incubation. Time-course studies indicated that the gut microbiota from I/R injured rats can catalyze the same reaction, but with a decreased reaction rate. The 16S rRNA sequencing technique was applied to uncover the community changes of gut microbiota. In addition, the metabolites of the three HAs exhibited greater activity in scavenging the DPPH radical and protected PC12 cells against oxidative damage.